A gazdagsági stagnálás 'színe' és fonákja: Jó az exporttöbblet és az adósságcsökkenés, de rossz a tőkekiáramlás és a beruházás-visszaesés? - László Halpern; Gábor Oblath (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
– Over the last few years Hungary has posted large and increasing surpluses in its trade balance. The country has also become a net lender to the rest of the world, revealed by the surplus in the current and capital account of the balance of payments. These developments are mirrored by significant deficits (capital outflows) recorded in the financial account, as well as by the fall in external indebtedness of both the private sector and the country as a whole. However, it is the poor performance of the economy regarding changes in income, consumption and investments - partly explained by deleveraging in the private sector - which underlies its external performance. Therefore, it makes little sense to rejoice over the surplus in the trade balance, while being unhappy about capital outflows and the low (decreasing) investment rate. These developments reveal different sides of the same story, where the various aspects are related to each other by macroeconomic accounting identities. While our paper aims to quantify these relationships in international comparison, it also makes the point that capital outflows should not be mixed up with "capital flight"; we found no evidence of the latter. We call attention to the fact that private investments, net of capital consumption, decreased to an extremely low level. Without a turn in investment activity, there is no hope for maintaining export growth and revitalizing domestic demand. However, the growth in investments is likely to decrease net exports, which may be a drag on economic growth.
Keywords: E65; F32; F34; 330; Hungary's macroeconomic developments; external debt; deleveraging; surplus on trade and current transactions; capital outflow